2021
DOI: 10.1021/acsaem.0c02270
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Diffusion of Cr2O3 into Different Phases of TiO2 upon Annealing

Abstract: Chromium oxide (Cr 2 O 3 ) can be used as a protective layer for photocatalysts to improve photocatalytic water splitting activity and is commonly photodeposited. However, it is not known how the conditions of the Cr 2 O 3 formation affect the formation of the protective layer and potential diffusion into the substrate onto which Cr 2 O 3 has been deposited. We have investigated the stability of Cr 2 O 3 photodeposited onto the surface of different crystal phases of TiO 2 with subsequent annealing at a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…The Ti2p spectrum of TiO 2 is composed of two narrow peaks at 458.6 and 464.2 eV corresponding to the spin–orbit split 2p 3/2 and 2p 1/2 sublevels, respectively. These positions coincide with the reported BE’s for Ti 4+ . , In the spectrum of the CTO sample, the two peaks are considerably broader, but they appear practically in the same positions as in TiO 2 . The absence of any detectable shift or shoulder at the low-BE side indicates that the presence of Ti 3+ ions must be very small.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The Ti2p spectrum of TiO 2 is composed of two narrow peaks at 458.6 and 464.2 eV corresponding to the spin–orbit split 2p 3/2 and 2p 1/2 sublevels, respectively. These positions coincide with the reported BE’s for Ti 4+ . , In the spectrum of the CTO sample, the two peaks are considerably broader, but they appear practically in the same positions as in TiO 2 . The absence of any detectable shift or shoulder at the low-BE side indicates that the presence of Ti 3+ ions must be very small.…”
Section: Resultssupporting
confidence: 88%
“…These positions coincide with the reported BE's for Ti 4+ . 45,46 In the spectrum of the CTO sample, the two peaks are considerably broader, but they appear practically in the same positions as in TiO 2 .…”
Section: ■ Methodsmentioning
confidence: 99%
“…In our previous work, the Cr 2p peak was described and fitted using a fixed relation between the intensity of the Ti 2p 3/2 and the Ti 2s loss peak. 59 The Cr 2p 3/2 peak is found at 577.4 AE 0.2 eV, which can be identified from literature reference data as being Cr(OH) 3 . 60 It should be noted that this is different to the binding energy of Cr 2 O 3 and will be discussed below (vide infra).…”
Section: Paper Materials Advancesmentioning
confidence: 89%
“…It was fitted by including the Ti 2s energy loss peak, which occurs in the same energy region. In our previous work, the Cr 2p peak was described and fitted using a fixed relation between the intensity of the Ti 2p 3/2 and the Ti 2s loss peak 59 . The Cr 2p 3/2 peak is found at 577.4 ± 0.2 eV, which can be identified from literature reference data as being Cr(OH) 3 60 .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Chromium­(III) oxide (Cr 2 O 3 ), the most stable oxide of chromium, naturally occurs as eskolaite mineral . Cr 2 O 3 is a rigid and fragile material that has a hexagonal crystal structure, which has been used in many applications, such as lithium-ion batteries, supercapacitors, gas sensors, and magnetoelectric data storage. Several studies have shown that Cr 2 O 3 exhibits high electrocatalytic activity and long-term stability for HER. According to previous reports, nanostructured Cr 2 O 3 materials are prepared using various methods, such as chemical vapor deposition, the sol–gel method, physical vapor deposition, the microwave oven method, electrostatic spray deposition, and the precipitation technique. , The electrochemical technique, among other applications, is advantageous because it is inexpensive, straightforward, and applicable under ambient conditions. No studies have reported on the electrochemical synthesis of Cr 2 O 3 nanostructures directly on the electrode surface via potentiometric deposition using a three-electrode cell system.…”
Section: Introductionmentioning
confidence: 99%